Spinel magnesium ferrite (MgFe2O4): a glycine-assisted colloidal combustion and its potentiality in gas-sensing application - Nadargi, Digambar; Umar, Ahmad; Nadargi, Jyoti; Patil, Jayvant; Mulla, Imtiaz; Akbar, Sheikh; Suryavanshi, Sharad (Chemosensors, 2022)
Herein, we describe the facile synthesis of spinel MgFe2O4 ferrite and its potential use as a gas sensor using a straightforward and reliable sol-gel approach, i.e., the glycine-assisted auto-combustion route. The novelty in obtaining the sensing material via the auto-combustion route is its inherent simplicity and capability to produce the material at an industry scale. The said cost-effective process makes use of simple metal salts (Mg and Fe-nitrates) and glycine in an aqueous solution, which leads to the formation of spinel MgFe2O4 ferrite. A single-phase crystallinity with crystallite sizes ranging between 36 and 41 nm was observed for the synthesized materials using the X-ray diffraction (XRD) technique. The porous morphologies of the synthesized materials caused by auto-ignition during the combustion process were validated by the microscopic investigations. The EDS analysis confirmed the constituted elements such as Mg, Fe, and O, without any impurity peaks. The gas-sensing ability of the synthesized ferrites was examined to detect various reducing gases such as LPG, ethanol, acetone, and ammonia. The ferrite showed the highest response (>80%) toward LPG with the response and recovery times of 15 s and 23 s, respectively. Though the sensor responded low toward ammonia (similar to 30%), its response and recovery times were very quick, i.e., 7 s and 9 s, respectively. The present investigation revealed that the synthesized ferrite materials are good candidates for fabricating high-performance sensors for reducing gases in real-world applications.
Keywords: Gas sensors; glycine combustion; MgFe2O4; reducing gases

Bismuth ferrite based acetone gas sensor: evaluation of graphene oxide loading - Ghadage, Pandurang; Shinde, K. P.; Nadargi, Digambar; Nadargi, Jyoti; Shaikh, Hamid; Alam, Mohammad Asif; Mulla, Imtiaz; Tamboli, Mohaseen S.; Park, J. S.; Suryavanshi, Sharad (RSC Advances, 2024)
We report a BiFeO3/graphene oxide (BFO/GO) perovskite, synthesized using a CTAB-functionalized glycine combustion route, as a potential material for acetone gas sensing applications. The physicochemical properties of the developed perovskite were analysed using XRD, FE-SEM, TEM, HRTEM, EDAX and XPS. The gas sensing performance was analysed for various test gases, including ethanol, acetone, propanol, ammonia, nitric acid, hydrogen sulphide and trimethylamine at a concentration of 500 ppm. Among the test gases, the developed BFO showed the best selectivity towards acetone, with a response of 61% at an operating temperature of 250 degrees C. All the GO-loaded BFO samples showed an improved gas sensing performance compared with pristine BFO in terms of sensitivity, the response/recovery times, the transient response curves and the stability. The 1 wt% GO-loaded BiFeO3 sensor showed the highest sensitivity of 89% towards acetone (500 ppm) at an operating temperature of 250 degrees C. These results show that the developed perovskites have significant potential for use in acetone gas sensing applications. CTAB-functionalized glycine combustion yields BiFeO3/graphene oxide (BFO/GO) perovskite for acetone gas detection.